Réponses

2013-10-12T18:27:29+02:00
A = 1/x + 1/x-5
A = 1*(x-5) / x(x-5)  + 1*x / (x-5)*x
A = x-5+x  /  x(x-5)
A = 2x-5 / x(x-5)

B = 2/(x+1) + 1/(x-1)
B = 2(x-1) / (x+1)(x-1)  +  (x+1) / (x-1)(x+1) 
B = 2x-2+x+1  /  (x+1)(x-1)
B = 3x-1  /  (x+1)(x-1)

C = 5/(x+4)  -  1/(x-3)
C = 5(x-3) / (x+4)(x-3)  -  (x+4) / (x-3)(x+4)
C = 5(x-3)-(x+4)  /  (x+4)(x-3)
C = 5x-15-x-4  /  (x+4)(x-3)

D = 3/x  - (x+1)/(x-1)
D = 3(x-1)/x(x-1)  -  x(x+1)/(x-1)x
D = 3(x-1)-x(x+1)  /  x(x-1)
D = 3x-3-x²-x  /  x(x-1)
D = -x²+2x-3  /  x(x-1)
merci beaucoup !
de rien, j'ai le même livre que toi donc c'est plus simple